2020
DOI: 10.1111/anae.15117
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of dexmedetomidine on postoperative behaviour change in children: a randomised controlled trial

Abstract: Children may develop changes in their behaviour following general anaesthesia. Some examples of negative behaviour include temper tantrums and nightmares, as well as sleep and eating disorders. The aim of this study was to determine whether dexmedetomidine reduces the incidence of negative behaviour change after anaesthesia for day case surgery in children aged two to seven years. Children were randomly allocated to one of three groups: a premedication group received 2 mg.kg-1 intranasal dexmedetomidine; an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 15 publications
1
30
1
Order By: Relevance
“…There was weak correlation between the PHBQ‐AS and the SDQ on day 3, moderate correlation on day 14, and weak‐to‐moderate correlation on day 28. These results are not as convincing as previously reported when the PHBQ‐AS was compared to the Functional Disability Inventory (Pearson's r = 0.49) 2 . One explanation for the poor correlation observed is that the SDQ has not been shown to have construct validity with respect to surgery.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…There was weak correlation between the PHBQ‐AS and the SDQ on day 3, moderate correlation on day 14, and weak‐to‐moderate correlation on day 28. These results are not as convincing as previously reported when the PHBQ‐AS was compared to the Functional Disability Inventory (Pearson's r = 0.49) 2 . One explanation for the poor correlation observed is that the SDQ has not been shown to have construct validity with respect to surgery.…”
Section: Discussioncontrasting
confidence: 80%
“…The reliability results for the PHBQ‐AS in this study are in line with what has previously been reported. The original study describing the development of the PHBQ‐AS calculated a Cronbach's alpha of 0.80 based on results from a database of 1064 patients from the United States 2 . Our study found a Cronbach's alpha of 0.79 and split‐half correlation with Spearman Brown adjustment of 0.85.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…We evaluated the quality of the literature and selected high-quality literature as the inclusion criteria for research. [6][7][8][11][12][13]20,[26][27][28][29][30][31][32]…”
Section: Introductionmentioning
confidence: 99%